Prevalence and treatment of diabetes and pre-diabetes in a real-world heart failure population: a single-centre cross-sectional study - Mattias Brunström; Krister Lindmark; Helena Norberg; Erik Håkansson; Sara Själander (Open Heart, 2022)
Aims The aim of this study was to investigate a real-world heart failure (HF) cohort regarding (1) prevalence of known diabetes mellitus (DM), undiagnosed DM and pre-diabetes, (2) if hf treatment differs depending on glycaemic status and (3) if treatment of DM differs depending on HF phenotype.Methods All patients who had received a diagnosis of HF at Umeå University Hospital between 2010 and 2019 were identified and data were extracted from patient files according to a prespecified protocol containing parameters for clinical characteristics, including echocardiogram results, comorbidities, fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) values. Patients’ HF phenotype was determined using the latest available echocardiogram. The number of patients with previous DM diagnosis was assessed. Patients without a previous diagnosis of DM were classified as non-DM, pre-diabetes or probable DM according to FPG and HbA1c levels using WHO criteria.Results In total, 2326 patients (59% male, mean age 76±13 years) with HF and at least one echocardiogram were assessed. Of these, 617 (27%) patients had a previous diagnosis of DM. Of the 1709 patients without a previous diagnosis of DM, 1092 (67%) patients had either an FPG or HbA1c recorded, of which 441 (41%) met criteria for pre-diabetes and 97 (9%) met criteria for probable diabetes, corresponding to 19% and 4% of the entire cohort, respectively. Patients with HF and diabetes were more often treated with diuretics and beta blockers compared with non-DM patients (64% vs 42%, p<0.001 and 88% vs 83%, p<0.001, respectively). There was no difference in DM treatment between HF phenotypes.Conclusions DM and pre-diabetes are common in this HF population with 50% of patients having either known DM, probable DM or pre-diabetes. Patients with HF and DM are more often treated with common HF medications. HF phenotype did not affect choice of DM therapy.